Medicine in Iran - Ebrahimnejad, H. author. aut Link
XIV, 268 p.
Keywords: This book traces how medicine in modern Iran was both theoretically and institutionally transformed in the 19th and 20th centuries. It explores the process by which local physicians, in a non-colonial context, assimilated the emerging "modern medicine" and the institutional devices that accommodated this transition.